The Relationship between Positive-Negative Interaction Ratio and Marital Satisfaction - Adi Dinardinata; Prasetyo Budi Widodo; Tosina Sagala (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
This study aimed to determine the relevance of positive-negative interaction ratio used as the predictor of marital satisfaction in Indonesia. The research sample was taken using purposive sampling technique. The participants of this study were 402 people who were asked to fill out an online questionnaire, thus the data were analyzed using correlational analysis. Data collection used an adaptation of the ENRICH Martial Satisfaction Scale and the Positive-Negative Ratio Scale. Data analysis used was simple regression analysis. The results of the analysis showed the correlation coefficient rxy = 0.253 with a significance level of p = 0.000 (p<0.05). In conclusion, there was a significant positive relationship between the ratio of positive-negative interactions and marital satisfaction in married couples who lived in Indonesia. The effective contribution of the positive-negative interaction ratio to marital satisfaction was 6.4%, while the rest was another undisclosed factor.